Psycho-Oncology, Psychosocial Problems and Measurement Methods - Beyhan Bag (Psikiyatride Güncel Yaklaşımlar, 2012)
It is not possible to conceive psycho-oncology separately from modern oncology. It is expected from medical personnel to realize patients’ psycho-social needs and to possess knowledge about the demanding psycho-oncologic treatment for patients if it is needed. According to World Cancer Report statistics, the oncology personnel lack ability to determine the psycho-social needs of cancer patients and their families. For the medical personnel that work in oncology services, it is inevitable to raise the awareness of the cancer patients’ psychosocial needs and to arrange in-service trainings about therapeutic negotiation techniques. The other step in the process of determining the psychological treatment and care requirements could be the improvement and execution of the standard psychological scanning tests applied to the cancer patients who are on the first level of diagnosis and treatment. It is important for the medical staff working with cancer patients to have a certain point of view concerning these issues. For this purpose, the present study focuses on the psychosocial problems that cancer patients might experience and on the evaluation techniques which are used in psycho-oncology.